Relationships between highly skilled golfers' clubhead velocity and vertical ground reaction force asymmetry during vertical jumps and an isometric midthigh pull - Wells, J. E.; Mitchell, A. C.; Charalambous, L. H.; Fletcher, I. M. (The Journal of Strength and Conditioning Research, 2020)
Clubhead velocity (CHV) is a commonly measured variable within golf due to strong associations with increased drive distance. Previous research has revealed significant relationships between CHV and vertical ground reaction force (vGRF) variables during bilateral tasks including a countermovement jump (CMJ), squat jump (SJ), drop jump (DJ), and isometric midthigh pull (IMTP). Asymmetries have been linked to performance outcomes in a number of sports; however, few studies have assessed asymmetries within golf. The current study, therefore, examined the relationships between CHV and vGRF asymmetries for CMJ positive impulse, SJ positive impulse, DJ positive impulse, and IMTP peak force (PF). Furthermore, the level of agreement for asymmetries between protocols was assessed by using Kappa coefficients. Fifty highly skilled (handicap =5) male golfers attended laboratory and range-based testing sessions. Positive impulse and PF were measured using a dual force platform system, with CHV measured using a TrackMan 3e launch monitor. There was no significant relationship (r = -0.14 to 0.22) between CHV and each of the vGRF asymmetry measures. Of the golfers tested, 26 had a "real" asymmetry in the CMJ, 18 had a "real" asymmetry in the SJ, 25 had a "real" asymmetry in the DJ, and 27 had a "real" asymmetry in the IMTP. Kappa coefficients indicated that asymmetries rarely favored the same limb (k = 0.06 to 0.39) with asymmetries varying for individual golfers between protocols. As such, asymmetries are neither beneficial nor detrimental to CHV but are inherently individual and dependent on the task.